Development and Validity of a Food Frequency _x000D_ Questionnaire for Assessing Vitamin C _x000D_ Intake in Turkish Adults - (:unkn) unknown (My University, 2020)
Objective: This study aimed to evaluate the validity of a food frequency questionnaire (FFQ) developed to determine vitamin C intake. Material and Methods: This research was carried out at Istanbul University Faculty of Dentistry between October 2017 and May 2018. There were 75 individuals in this study, who were 18-65 years old. In order to determine the level of vitamin C intake of individuals, a FFQ was formed which contains the consumption frequency and the amount of consumption of 83 foods and its language is Turkish. After the determination of the plasma ascorbic acid level (PAAL) of the individuals, the validity of the questionnaire was examined by Spearman correlation test, Bland Altman plot and kappa statistics. All statistical analysis were performed using the IBM SPSS Statistics 20 Software and statistically significant differences were determined using a p value <0.05. Results: A total of 75 people (31 male and 44 female) participated in this study, and the mean age was 35.69±10.35 years. The median PAAL was 7.94 mg/L, while the median intake of vitamin C was 136.84 mg/d. There was a positive correlation between PAAL and intake of vitamin C (r=0.41; p<0.001). The values of PAAL and intake of vitamin C calculated by FFQ were divided into quartiles, and the rate of the classifying into the same or adjacent quartile was 81.4%. Conclusion: In conclusion, this questionnaire can be used to determine intake of vitamin C in Turkish adults.

Amaç: Bu çalışma, C vitamini alımını belirlemek amacıyla _x000D_ geliştirilen bir besin tüketim sıklığı anketinin (food frequency question?naire: FFQ) geçerliliğini değerlendirmeyi amaçlamaktadır. Gereç ve _x000D_ Yöntemler: Bu çalışma, Ekim 2017 - Mayıs 2018 tarihleri arasında İs?tanbul Üniversitesi Diş Hekimliği Fakültesi’nde gerçekleştirilmiştir. _x000D_ Çalışmaya 18-65 yaş arasındaki 75 gönüllü birey katılmıştır. Bireylerin _x000D_ C vitamini alımlarını belirlemek için, toplam 83 besinin tüketim miktarı_x000D_ ve sıklığını içeren Türkçe bir besin tüketim sıklığı anketi oluşturulmuştur. _x000D_ Bireylerin plazma askorbik asit seviyelerinin belirlenmesinin ardından _x000D_ anketin geçerliliği Spearman korelasyon testi, Bland Altman grafiği ve _x000D_ kappa istatistiği ile incelenmiştir. Tüm istatistiksel analizler IBM SPSS _x000D_ Statistics 20 yazılımı kullanılarak yapılmış ve p<0,05 değeri istatistik?sel olarak anlamlı kabul edilmiştir. Bulgular: Çalışmaya katılan 75 _x000D_ kişiden 31'i (%41,3) erkek, 44'ü (%58,7) kadındır. Medyan plazma _x000D_ askorbik asit seviyesi 7,94 mg/L iken, medyan C vitamini alımı 136,84 _x000D_ mg/gün’dür. Plazma askorbik asit seviyesi ile C vitamini alımı arasında _x000D_ pozitif bir korelasyon bulunmuştur (r=0,41; p<0,001). Plazma askor?bik asit düzeyleri ve FFQ ile hesaplanan C vitamini alım miktarları_x000D_ çeyreklere ayrılmış; aynı veya bitişik çeyrekte sınıflandırma oranı_x000D_ %81.4 olarak bulunmuştur. Sonuç: Sonuç olarak, bu anket yetişkin _x000D_ Türklerde C vitamini alım düzeyini belirlemek için kullanılabilir.
Yetişkin Türklerde C Vitamini Alımının Değerlendirilmesine Yönelik Besin Tüketim Sıklığı Anketinin Geliştirilmesi ve Geçerliliği